A case report of leptospirosis complicated by severe pulmonary hemorrhage treated with venovenous extracorporeal membrane oxygenation - Yang, Li Wen; Tang, Xiao Gang; Xiong, Bin; Zhang, Yunli (Frontiers in Medicine, 2025)
Leptospirosis is a zoonotic disease with diverse clinical manifestations, and its severe form can lead to life-threatening complications such as pulmonary hemorrhage. We present a novel case of a 57-year-old woman with leptospirosis who developed severe pulmonary hemorrhage and acute respiratory distress syndrome (ARDS) and was successfully managed with early venovenous extracorporeal membrane oxygenation (VV-ECMO), minimal anticoagulation, and lymphoplasmacyte exchange (LPE). This case highlights the importance of early ECMO initiation, individualized anticoagulation, and immunomodulatory therapy in improving outcomes for patients with leptospiral pulmonary hemorrhage syndrome (LPHS), a condition with mortality exceeding 50%. To our knowledge, this is the first reported case combining VV-ECMO with LPE in LPHS, offering a new therapeutic paradigm for critically ill patients at the intersection of infection and autoimmunity.